2008
DOI: 10.3945/jn.108.098665
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation of Rural Gambian Women during Pregnancy Does Not Affect Body Composition in Offspring at 11–17 Years of Age

Abstract: Fetal nutrition is thought to be an important determinant of later disease risk, although evidence from randomized-controlled trials in humans is lacking. We followed children born during a protein-energy supplementation trial to investigate to what extent this maternal supplement, which improved birth weight, influenced offspring body composition in adolescence. Subjects were 1270 Gambian children (659 boys, 611 girls) aged 11-17 y whose mothers had participated in the original cluster-randomized trial and ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…), but was not associated with the body composition of children at 11–17 years of age (Hawkesworth et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…), but was not associated with the body composition of children at 11–17 years of age (Hawkesworth et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…), but has not been associated with differences in offspring body composition at 11–17 years of age (Hawkesworth et al . ). In Indonesia, protein‐energy supplements resulted in a modest improvement in birthweight, and children were taller throughout the first 5 years (Kusin et al .…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, follow-up studies of nutrition intervention trials in pregnant women have shown an inconsistent relationship between early nutrition exposure and LBM of the offspring (9, 10, 30). A widely cited study from Guatemala showed a positive association of a high-energy, high-protein supplement provided to pregnant women and young children with the LBM of the offspring (girls only) during adolescence (9).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies around the world have since assessed the critical role of maternal nutrition on offspring outcomes at birth and in later life [33][34][35][36][37][38][39][40][41] . In India too, studies on maternal pre-pregnancy nutrition have contributed to the developmental origins evidence base.…”
Section: Prenatal Nutritionmentioning
confidence: 99%